Overview : a new perspective of earth - Grant, Benjamin (Amphoto Books, 2016)
This collection of satellite images of Earth provided by DigitalGlobe are annotated and reformated by Benjamin Grant to provide a new perspective of earth and an understanding of the impact of human activity on the planet. These images are inspired by the Daily Overview, an Instagram account established by the author.